2020
DOI: 10.1111/jcmm.15995
|View full text |Cite
|
Sign up to set email alerts
|

Strongylocentrotusnudos Egg Polysaccharide induces autophagy and apoptosis in leukaemia cells by regulating mitochondrial function

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Strongylocentrotus nudus is another kind of precious traditional Chinese medicine, which has the remarkable effect of anti-tumor ( 95 ). As a D-glucan containing an α-1, 4-linked backbone, and α-1, 3-linked branches, Strongylocentrotus nudus Egg Polysaccharide is extracted and purified from sea urchins’ eggs ( 96 ).…”
Section: Experimental and Clinical Trials On Hcc Of Tcm Polysaccharid...mentioning
confidence: 99%
See 1 more Smart Citation
“…Strongylocentrotus nudus is another kind of precious traditional Chinese medicine, which has the remarkable effect of anti-tumor ( 95 ). As a D-glucan containing an α-1, 4-linked backbone, and α-1, 3-linked branches, Strongylocentrotus nudus Egg Polysaccharide is extracted and purified from sea urchins’ eggs ( 96 ).…”
Section: Experimental and Clinical Trials On Hcc Of Tcm Polysaccharid...mentioning
confidence: 99%
“…Strongylocentrotus nudus is another kind of precious traditional Chinese medicine, which has the remarkable effect of anti-tumor (95).…”
Section: Strongylocentrotus Nudus Eggs Polysaccharidementioning
confidence: 99%
“…Under the circumstance that cells are stimulated, the structure of mitochondria could undergo a certain degree of shift to the pathological mode due to the highest sensitivity to the injuries among all subcelluar organelles [101]. Wang et al found that the abnormal structure of mitochondria in intestinal epithelial cells of mice with ulcerative colitis can be proportionally restored with the treatment of high dose of mycelium polysaccharide and the membrane were prone to be intact and less swollen [102].…”
Section: Morphological Alterationmentioning
confidence: 99%
“…Polysaccharides are natural biological macromolecules derived from fungi, marine organisms, plants, lichens, and animals (Ooi and Liu, 2000). Previous studies have shown that polysaccharides and polysaccharide-protein complexes exhibit significant anticancer activities and increase the efficacy of other small-molecule chemotherapy drugs (Zong et al, 2012;Zhang et al, 2017;Xie et al, 2019;Wang et al, 2020). Polysaccharides are superior in inhibiting tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%